2014
DOI: 10.5468/ogs.2014.57.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of estrogen receptor-α, progesterone receptor and calponin expression in gonadotrophin-releasing hormone agonist-sensitive and -resistant uterine fibroids

Abstract: ObjectiveThis study was aimed to compare immunohistochemical expression of estrogen receptor (ER)-α, progesterone receptor (PR), and calponin in gonadotrophin-releasing hormone agonist (GnRH-a)-sensitive and -resistant uterine fibroids.MethodsWe collected data retrospectively. The sensitive group consisted of women who had reduction in uterine volume greater than 40% following GnRH-a treatment. Uterine volume was either reduced by less than 10%, or was increased in the resistant group. A tissue microarray was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…These findings suggest that estrogens exert their pro-mitogenic effect by transcriptional mechanisms (Andersen et al, 1995;Pedeutour et al, 1998;Yin et al, 2007). There seems to be no difference in estrogen receptor-a (ERa) expression in GnRH agonist-sensitive and -resistant uterine fibroids (Kim et al, 2014). Proliferation of Eker rat-derived leiomyoma cell lines, which carry a germline mutation in the Tsc2 gene, is also stimulated by 17b-estradiol and inhibited by the selective estrogen receptor modulator (SERM) tamoxifen in vitro (Howe et al, 1995).…”
Section: Clinical Effects Of Estrogen and Progesterone Receptor Targeted Therapiesmentioning
confidence: 95%
“…These findings suggest that estrogens exert their pro-mitogenic effect by transcriptional mechanisms (Andersen et al, 1995;Pedeutour et al, 1998;Yin et al, 2007). There seems to be no difference in estrogen receptor-a (ERa) expression in GnRH agonist-sensitive and -resistant uterine fibroids (Kim et al, 2014). Proliferation of Eker rat-derived leiomyoma cell lines, which carry a germline mutation in the Tsc2 gene, is also stimulated by 17b-estradiol and inhibited by the selective estrogen receptor modulator (SERM) tamoxifen in vitro (Howe et al, 1995).…”
Section: Clinical Effects Of Estrogen and Progesterone Receptor Targeted Therapiesmentioning
confidence: 95%
“…Uterine leiomyoma increases the risk of abnormal bleeding, infertility, and pregnancy complications (16). It is generally accepted that this is a hormone-dependent disease, and that estrogen and progesterone greatly influence its development (17)(18)(19) through the activation of ER and PR, respectively. Previous studies indicated that ER-alpha and ER-beta might play different roles in the proliferation of uterine leiomyoma cells.…”
Section: Introductionmentioning
confidence: 99%